Evaluation and treatment of compulsive sexual behavior: current limitations and potential strategies - Zhu, Lu; Ma, Wenwen; Zhang, Rongqiu; Wang, Chao; Song, Bing; Cao, Yunxia; Li, Guanjian (Frontiers in Psychiatry, 2025)
AimDespite having been introduced into ICD-11, the appropriate classification and symptomatology of compulsive sexual behavior disorder (CSBD) remain controversial.MethodsIn this review, we examined the historical background, epidemiological status quo, comorbidities, neuroscience theories, current diagnoses, and treatment recommendations for CSBD. Additionally, we emphasized the limitations of the current research and the prospects for future work.ResultsPsychotherapy and cognitive-behavioral therapy are the preferred treatment methods for CSBD. Selective serotonin reuptake inhibitors and naltrexone are commonly used as “off-label” drugs. The diagnosis and treatment of patients with CSBD should integrate biological, psychological, and social factors with expertise in sexual medicine by employing a comprehensive and holistic therapeutic approach. This treatment aims not only to control abnormal sexual desires and behaviors but also to assist patients in achieving a healthy and satisfying sexual life and well-being.ConclusionFuture research should focus on understanding etiology, improving study population representation, correcting methodological flaws in treatment evaluation, enhancing clinician training in sexual medicine, and addressing patients’ addictions and sexual function issues. Narrowing these research gaps is crucial for improving clinical diagnosis and treatment levels and formulating targeted social intervention measures.